The lost gospel : the book of Q & Christian origins - Mack, Burton L. ([San Francisco, Calif.] : HarperSanFrancisco, 1993)
"This is the first full account of the lost gospel of Jesus' original followers, revealing him to be a Jewish Socrates who was mythologized into the New Testament Christ. Compiled by his followers during his lifetime, the Book of Q (from Quelle, German for source) became the prime foundation for the New Testament gospels. Once lost, it has been reconstructed through a century of scholarship. In presenting his own translation, Burton Mack explains how the text of Q was determined and explores the implications of the discovery that Jesus was transformed into the dying and rising messianic savior of Christianity by the New Testament gospels." "Instead of telling a dramatic story about Jesus' life as the Christian gospels do, the Book of Q contained only his sayings. The first followers of Jesus focused not upon his life and destiny, but on the social experiment called for by his teachings. Their book collected his proverbs, aphorisms, and parables to offer instruction in living authentically in the midst of a most confusing time." "In The Lost Gospel, Burton Mack puts forth the first popular translation of Q as scholarly consensus has reconstructed it; shows that Jesus' life story as presented in the New Testament gospels was fictionalized for theological purposes; reveals Jesus to be a countercultural teacher and leader - subsequently mythologized into the Christ of the New Testament; depicts Jesus' followers not as Christians, but as disciples of a wise, antiestablishment teacher; they did not believe him to be the son of God, believe that he rose from the dead, or gather to worship in his name and concludes that Christianity is a mythologized religion (like Buddhism and other religions) rooted in a historical figure and teachings that in reality are quite remote from conventional beliefs."--BOOK JACKET.
The discovery of a lost gospel -- The text of the lost gospel -- The recovery of a social experiment -- The reconception of christian origins -- The consequences.
Includes bibliographical references (p. 263-267) and index.
Keywords: Q hypothesis (Synoptics criticism); Christianity -- Origin